Human Resource Quality Development Strategy by the West Java Regional Legislative Council Through International Cooperation - Kevin Kleery Kumape; Indra Wisnu Wibisono; Sri Suwartiningsih (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study discusses the strategies for developing human resources (HR) implemented by the West Java Provincial Legislative Council through international partnerships and cooperation. In the context of globalization and increasingly intense regional competition, Human Resource Development has become one of the top priorities for enhancing regional competitiveness. The West Java Regional Legislative Council plays a role as a legislative body and a strategic actor in regional diplomacy (paradiplomacy) by establishing international relations to support capacity building in various sectors, particularly education, industry, and technology. This study employs a qualitative approach using document analysis, interviews, and secondary data analysis from various cooperation agreements, including those with Chungcheongnam-do Province, South Korea. The findings reveal that the international cooperation facilitated by The West Java Legislative Council not only enhances access to education and training for the youth of West Java but also opens opportunities for internships, student exchanges, and technology transfer aligned with the needs of the local industry. This strategy demonstrates synergy between legislative policies and regional development directions focused on improving human resource quality. Additionally, The West Java Legislative Council promotes integrating global values into the local context, enabling West Java's society to adapt more effectively to global dynamics. Thus, international cooperation effectively strengthens the foundation for sustainable and highly competitive human resource development in West Java.